Research and Fabrication of WO₃ Thin Film Sensors for C₂H₅OH Gas Sensing Application - Nguyen, Van Toan; Nguyen, Van Hieu (Old Journal, 2019)
Thin film of tungsten oxide was successfully fabricated from tungsten target by using reactive sputtering combining with lithography technology. The thickness, structure and morphology of the thin film were investigated by α-step, XRD and FE-SEM respectively. The gas sensing measurements of the WO₃ thin film sensors indicated that these sensors have a high sensitivity and quick response to C₂H₅OH. With the simple research method (using only two masks), the results of this study have a lot of potential for applying to C₂H₅OH gas sensor.